2021
DOI: 10.1186/s12903-020-01381-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and oral health-related quality of life 10 years after implant placement

Abstract: Background Implant survival and implant success (freedom of biologic complications) are important factors in assessing the success of implant therapy. However, these factors are not the only determinants. Patients’ satisfaction also plays a very important role in daily practice. Therefore, the aim of this study was to assess patients’ satisfaction regarding function (phonetics, chewing comfort, stability, cleanability) and aesthetics in patients treated with XiVE and Frialite implants in a priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
2
34
0
2
Order By: Relevance
“…However, this study did not state whether patients had peri-implant mucositis. Both studies, by Romandini et al 24 and Wang et al, 25 found no difference between the presence and absence of peri-implantitis in terms of total OHIP values. In patients' mean age was 63.7 (range not specified) in Romandini et al 24 and 63.4 (ranging from 28 to 86) in Wang et al's 25 study.…”
Section: Ta B L E 2 Answers To Ohip-14 Questionsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, this study did not state whether patients had peri-implant mucositis. Both studies, by Romandini et al 24 and Wang et al, 25 found no difference between the presence and absence of peri-implantitis in terms of total OHIP values. In patients' mean age was 63.7 (range not specified) in Romandini et al 24 and 63.4 (ranging from 28 to 86) in Wang et al's 25 study.…”
Section: Ta B L E 2 Answers To Ohip-14 Questionsmentioning
confidence: 88%
“…Both studies, by Romandini et al 24 and Wang et al, 25 found no difference between the presence and absence of peri-implantitis in terms of total OHIP values. In patients' mean age was 63.7 (range not specified) in Romandini et al 24 and 63.4 (ranging from 28 to 86) in Wang et al's 25 study. Neither study was confined to geriatric populations; therefore, the literature contains no studies that specifically focus on evaluating the effect of peri-implant disease on quality of life in the geriatric population, especially in groups including perimucositis.…”
Section: Ta B L E 2 Answers To Ohip-14 Questionsmentioning
confidence: 88%
See 1 more Smart Citation
“…[3] Dental implant treatment; it has taken its place in the literature as a treatment method that is mostly welcomed by patients and the results are better than other prosthetic methods. [4][5][6][7][8] In over implant prostheses; thanks to the adequate retention and stability of the prosthesis, functional prostheses can be made and thus the quality of life of the patient can be improved. [9] In short, dental implant treatment is accepted as the gold standard today for the elimination of tooth losses.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the material in the oral cavity, i.e., in direct contact with tissues, places special demands on this group of biomaterials regarding their physicochemical and biological properties, i.e., biocompatibility, local and general harmlessness to the organism [ 18 , 21 , 22 ], resistance to the effects of physicochemical factors in the oral cavity [ 21 ] and biophysical indifference [ 18 , 19 ]. In addition, the accuracy in mimicking natural tooth shapes [ 19 ], stability of mechanical properties [ 19 , 22 ], ease processing [ 21 , 23 ], appropriate aesthetics [ 19 , 24 ], and finally a moderate price [ 19 , 23 ] are further requirements that need to be met. The first phenomenon that occurs after the introduction of the biomaterial into the oral cavity is the formation of a biofilm on its surface [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%